Detection and Analysis of MOSH/MOAH Contamination in Edible Vegetable Oils: A Comprehensive Review - Kasturi Indiran; Nur Hidayah Azeman; Nadhratun Naiim Mobarak; Ahmad Ashrif A. Bakar (Malaysian Journal of Science (MJS), 2025)
Consuming edible vegetable oil (EVO) is highly beneficial for human health due to its abundant nutrients, yet it might pose a risk if contaminated. Common pollutants such as mycotoxins, pesticides, heavy metals, and mineral oil will likely occur during harvesting, industrial processing, and environmental pathways. This review focuses on mineral oil, a type of petrogenic pollutant that can be further classified into two subgroups: mineral oil saturated hydrocarbon (MOSH) and mineral oil aromatic hydrocarbon (MOAH). Due to its significant consumption, exposure to MOSH/MOAH in EVO has a detrimental impact on human health, to the point that both subgroups are considered hazardous. Indeed, MOSH can bioaccumulate in certain organs, and certain MOAH compounds have a strong potential to cause cancer. The European Food Safety Association (EFSA) has established standards for vegetable oil, updated in 2022, which provide a maximum limit of 13 mg MOSH/kg and 0.5 mg MOAH/kg. Additionally, a pragmatic monitoring method is implemented, including identifying and evaluating MOSH/MOAH presence in the specific matrix using analytical techniques that can accurately measure their quantities. Despite the existence of various techniques, the Liquid Chromatography–Gas Chromatography-Flame Ionisation Detector (LC-GC-FID) technique stands out for its adaptability, efficiency, sensitivity, and excellent reproducibility, even in the presence of complicated matrix and analyte. Therefore, this study comprehensively explains the operating principle, sample preparation, column selection, and assessment results. Various advanced techniques were employed to detect, measure, and distinguish individual MOSH/MOAH structures. These methods involved using additional instruments; in certain instances, innovative approaches were also implemented. In this review, the focus is on elucidating the presence of MOSH/MOAH contamination in EVO and delving into the LC-GC-FID method, the prevailing approach for quantification, with a comprehensive exploration of its intricacies.